(untitled) (Research, Society and Development, 2021)
This study aimed to present dental care for oral manifestations that may occur after antineoplastic treatment. As a methodology, a search was carried out in the databases Pubmed, Lilacs and Bibliography of Brazilian Dentistry (BBO), in addition to book chapters and dissertations. Based on the studies analyzed, the most frequent oral changes were found and proposed some forms of dental treatment to support these individuals, who received antineoplastic therapy, in order to provide health professionals with therapeutic options that improve the quality of life of individuals with cancer, after analyzing the selected articles, we concluded that the participation of dental professionals in comprehensive cancer therapy is essential, the dental surgeon must be trained to care for cancer patients, when receiving it before the start of therapies, you should perform a clinical and radiographic evaluation of your mouth to identify and treat any and all outbreaks of infection at this stage.